2021
DOI: 10.5430/ijfr.v12n2p164
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior in the Information Economy: Generation Z

Abstract: The article examines the features of consumer behavior of Generation Z, the largest consumer group in the world today. The authors highlight the ability and willingness to purchase goods and services online as the main trends in changing consumer behavior, while the main means of getting information, choosing a product (service), and paying for a purchase today are smartphones and tablets actively used by representatives of Generation Z. Generation Z has been determined to be digital consumers boldly shopping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Previous research has indicated that Generation Z has certain characteristics that differentiate it from other generations; for example, its expectations for purchasing behavior are different from those of previous generations because its members' digitally literate consumption makes them highly informed, more pragmatic, and more capable of making analytical decisions than representatives of previous generations are (Grigoreva et al, 2021). In addition, Generation Z has been associated with low confidence and low self‐esteem (Writer, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that Generation Z has certain characteristics that differentiate it from other generations; for example, its expectations for purchasing behavior are different from those of previous generations because its members' digitally literate consumption makes them highly informed, more pragmatic, and more capable of making analytical decisions than representatives of previous generations are (Grigoreva et al, 2021). In addition, Generation Z has been associated with low confidence and low self‐esteem (Writer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…those of previous generations because its members' digitally literate consumption makes them highly informed, more pragmatic, and more capable of making analytical decisions than representatives of previous generations are (Grigoreva et al, 2021). In addition, Generation Z has been associated with low confidence and low self-esteem (Writer, 2017).…”
mentioning
confidence: 99%
“…Previous research indicates that this generation has been the least studied of all the others, making it the least understood (Dolot, 2018). One of the most distinguishing characteristics of generation Z is that their expectations for purchasing behaviour are significantly different than those of previous generations (Grigoreva et al , 2021). Additionally, Seemiller and Grace (2018) state that this generation is looking for opportunities for growth in their choices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to (Peighambari et al, 2016) consumer behavior is a diverse and broad perspective due to changes in society, economy and technology that affect the way consumers behave. As for product information indicators and choosing product options (Grigoreva et al, 2021) .…”
Section: Consumer Behaviormentioning
confidence: 99%